THE IMPACT BUDGETARY PARTICIPATION TOWARD MANAGERIALS PERFORMANCE AND JOB SATISFACTION : JOB RELEVANT INFORMATION (JRI) AND BUDGET GOAL COMMITMENT AS INTERVENING VARIABLE - Panghegar, Dwias; Rosyati, Rosyati (Universitas Muhammadiyah Magelang, 2009)
The current study uses job relevant information and budget goal commitment as intervening variable between relationship participative budgeting toward managerâs performance and job satisfaction. Data for this study were collected using a questionnaire survey sent to 114 middle managers and lower manajer working in 29 service companies in the Magelang. At least 29 manager who has participated in this research, also same to 66% response rate. The study employs a multiple regression model to analyze the hiphotesis and assist by the SPSS 12.00 from windows programs. The result of this research is showed that the relationship between participative budgeting and managerial performance statistically significant,  the relationship between participative budgeting and job satisfaction statistically significant,  job-relevant information and goal commitment budgeting âas intervening variablesâstatistically, significantly affect the relationship between participative budgeting and managerial performance,  job-relevant information and goal commitment budgeting - as intervening variables- statistically, significantly affect the relationship between participative budgeting and budget goal commitment does not statistically significantly influence job satisfaction.